PERANCANGAN PROGRAM PEMINJAMAN DAN PENGEMBALIAN BUKU PADA PERPUSTAKAAN SMAN 1 MALINGPING BANTEN - Dian Ardiansyah; Dewi Yuliandari; Denny Vian Alfiandi; Mareanus Lase (Jurnal Akrab Juara, 2019)
Increasingly rapid technological development has given rise to a very broad impact for the various aspects of life both among schools, government agencies and individuals. Most of the school library is in need of a good data processing system, in order to facilitate the preparation of report and presentation of data. For example, to know the data of each book and determine whether there is a change in any part of the placement of the book, so when there is no hard data requests in search and does not inhibit the processing. Making this program using Microsoft Visual Basic 6.0, XAMPP and Crystal Report. The program is expected that the author can resolve any problems that may occur when manually borrowing. From then making of this final report can be deduced with this programming, charging and data storage will become easier and peaceful. Preparation documents and transaction process will be efficient and effevtive because of the computer all the data can be processed accurately and exact. With a use computers will save data storage and data retrieval will be faster and simple. Application computer programming can help facilitate the work of man in dealing with a process that is sometimes difficult when done by humens